(untitled) (Research, Society and Development, 2025)
Assistance for oncological patients with colostomies involves care that goes beyond the physical aspect, encompassing emotional, social, nutritional, and psychological challenges following the colostomy procedure. This study aimed to analyze the challenges and adaptation strategies of these patients, focusing on physical, emotional, social, dietary, and multiprofessional support dimensions. It is a quantitative, descriptive study conducted with 20 patients undergoing treatment at the Oncology Center of Cascavel (CEONC). Data collection was carried out through semi-structured questionnaires. The research showed a balance between genders and a predominance of participants aged 56 to 65 years. Most had temporary colostomies (65%) and good physical adaptation, with 85% reporting little or no pain. Emotionally, 65% reported discomfort and 45% sadness, with only 40% of those who reported depression receiving psychological support. All participants received appropriate nursing guidance, although 70% still rely on assistance. Among the professionals identified as essential, the psychologist (50%), the stomatherapy nurse (45%), and the nutritionist (5%) stood out, highlighting the importance of multiprofessional support.